2005
DOI: 10.1007/s10350-004-0828-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-α (Infliximab) Used as Induction Treatment in Case of Active Proctitis in a Multistep Strategy Followed by Definitive Surgery of Complex Anal Fistulas in Crohn's Disease: A Preliminary Report

Abstract: A multistep strategy followed by definitive surgery for the treatment of complex perianal fistulas in patients with Crohn's disease is a promising treatment modality. The preliminary results of this study suggest that Infliximab treatment has a beneficial additive effect in the multistep treatment followed by definitive surgery of complex anal fistulas and active proctitis in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 32 publications
3
42
1
4
Order By: Relevance
“…In a small prospective study, a multistep strategy (including three infliximab infusions in case of active proctitis, 3 months after placement of setons) achieved a response rate exceeding 97% after 1 year in 17 highly selected patients. 24 The standardized multimodal approach described here combining infliximab therapy with a surgical procedure allowed a 74% complete response rate which favorably compares with the 48% response rate obtained in the ACCENT II trial. 15 These quite satisfactory results were obtained despite inclusion of more severe patients, i.e., with anorectal stricture or with recto-vaginal fistula tracks.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a small prospective study, a multistep strategy (including three infliximab infusions in case of active proctitis, 3 months after placement of setons) achieved a response rate exceeding 97% after 1 year in 17 highly selected patients. 24 The standardized multimodal approach described here combining infliximab therapy with a surgical procedure allowed a 74% complete response rate which favorably compares with the 48% response rate obtained in the ACCENT II trial. 15 These quite satisfactory results were obtained despite inclusion of more severe patients, i.e., with anorectal stricture or with recto-vaginal fistula tracks.…”
Section: Discussionmentioning
confidence: 77%
“…According to previous studies and the time to heal the rectal mucosa, time to the surgical procedure for setons removal was standardized here to between the second and the third infliximab infusion. 18,23,24,28,29 The results suggest that this second surgical step is safe and effective when performed 1 month after starting infliximab therapy.…”
Section: Discussionmentioning
confidence: 90%
“…48,49 These findings demonstrate the importance of quiescent rectal disease for the success of this procedure. 52 The timing of flap advancement after anti-TNF-alpha therapy is controversial, but waiting 1 month may be appropriate to allow immunosuppression to moderate.…”
Section: Anorectal Diseasementioning
confidence: 99%
“…Moreover, various uncontrolled series are reported in the literature, which evaluate the effectiveness of combination J Ultrasound (2015) 18:19-35 29 therapy [71,[116][117][118][119]. In two prospective, larger studies with a median follow-up of 20 months, complete clinical remission was reported in 29-47 % of patients and a partial response in 42-53 % of patients [120,121].…”
Section: Combination Medical and Surgical Therapymentioning
confidence: 99%